Eye lens weight and nitrogen content predict beef animal age - C.R. Raines; Melvin C. Hunt; James J. Higgins; James L. Marsden; Michael E. Dikeman; John A. Unruh (Kansas Agricultural Experiment Station Research Reports, 2007)
With the emergence of Bovine spongiform encephalopathy (BSE) and the necessity to guarantee cattle ages to meet export requirements of some countries, the need to accurately determine age is paramount to the worldwide beef industry. The United States Department of Agriculture (USDA) estimates that only approximately 5% of U.S. beef cattle have documented chronological ages. Several methods for determining or predicting cattle age exist, including vertebra ossification, lean color, and dentition. Current systems can be criticized due to their subjectivity and subsequent inherent variability. Because concerns exist about current methods of determining cattle age, we investigated the use of the bovine eye lens to determine cattle age. Researchers have found that the eye lens grows continually throughout life, and that all animals exhibit a similar lens growth pattern. Lens properties, specifically weight and nitrogen content, are highly related to age of kangaroos, and are also minimally affected by diet and environment for swine. We hypothesized that eye lens weight and nitrogen content, alone or in combination, would more accurately predict the chronological age of cattle than dentition or carcass maturity.
Keywords: Cattlemen& #x27; s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; Eye lens weight; Nitrogen